Reliable Delay Constrained Multihop Broadcasting in VANETs. (19th September 2010) - Koubek Koubek, Martin Martin; Rea Rea, Susan Susan; Pesch Pesch, Dirk Dirk
Abstract : Vehicular communication is regarded as a major innovative feature for in-car technology. While improving road safety is unanimously considered the major driving factor for the deployment of Intelligent Vehicle Safety Systems, the challenges relating to reliable multi-hop broadcasting are exigent in vehicular networking. In fact, safety applications must rely on very accurate and up-to-date information about the surrounding environment, which in turn requires the use of accurate positioning systems and smart communication protocols for exchanging information. Communications protocols for VANETs must guarantee fast and reliable delivery of information to all vehicles in the neighbourhood, where the wireless communication medium is shared and highly unreliable with limited bandwidth. In this paper, we focus on mechanisms that improve the reliability of broadcasting protocols, where the emphasis is on satisfying the delay requirements for safety applications. We present the Pseudoacknowledgments (PACKs) scheme and compare this with existing methods over varying vehicle densities in an urban scenario using the network simulator OPNET.